Design and Testing of VHF Eggbeater Antenna - Dangol, Sunil; Hyongoju, Susan; Sah, Bindeshwor Kumar; Buddhacharya, Sarbagya; Sayanju, Sirash (Journal of Science and Technology, 2024)
In the field of satellite communication, the design and performance of VHF eggbeater antennas play a pivotal role in establishing reliable links with low Earth orbit (LEO) satellites. This paper presents a detailed study on the design, testing, and verification of a VHF eggbeater antenna optimized for 145.8 MHz; a frequency commonly used for satellite communication. The design methodology involves precise calculations of antenna dimensions, simulation for performance optimization, and practical implementation using a NanoVNA for characterization. Experimental results include SWR curves, impedance measurements, and radiation pattern analysis, confirming the antenna’s efficacy in achieving circular polarization and omnidirectional coverage suitable for LEO satellite communication. Verification tests demonstrate robust signal transmission capabilities over varying distances and environmental conditions. This study contributes valuable insights into enhancing antenna performance for satellite communication applications, paving the way for further advancements in antenna technology.